Endothelial Immune Activation by Medin: Potential Role in Cerebrovascular Disease and Reversal by Monosialoganglioside‐Containing Nanoliposomes. Issue 2 (21st January 2020) - Karamanova, Nina; Truran, Seth; Serrano, Geidy E.; Beach, Thomas G.; Madine, Jillian; Weissig, Volkmar; Davies, Hannah A.; Veldhuizen, Jaimeson; Nikkhah, Mehdi; Hansen, Michael; Zhang, Weiyang; D'Souza, Karen; et al.
Abstract : Background: The function of medin, one of the most common human amyloid proteins that accumulates in the vasculature with aging, remains unknown. We aim to probe medin's role in cerebrovascular disease by comparing cerebral arterial medin content between cognitively normal and vascular dementia (VaD) patients and studying its effects on endothelial cell (EC) immune activation and neuroinflammation. We also tested whether monosialoganglioside‐containing nanoliposomes could reverse medin's adverse effects. Methods and Results: Cerebral artery medin and astrocyte activation were measured and compared between VaD and cognitively normal elderly brain donors. ECs were exposed to physiologic dose of medin (5 μmol/L), and viability and immune activation (interleukin‐8, interleukin‐6, intercellular adhesion molecule‐1, and plasminogen activator inhibitor‐1) were measured without or with monosialoganglioside‐containing nanoliposomes (300 μg/mL). Astrocytes were exposed to vehicle, medin, medin‐treated ECs, or their conditioned media, and interleukin‐8 production was compared. Cerebral collateral arterial and parenchymal arteriole medin, white matter lesion scores, and astrocyte activation were higher in VaD versus cognitively normal donors. Medin induced EC immune activation (increased interleukin‐8, interleukin‐6, intercellular adhesion molecule‐1, and plasminogen activator inhibitor‐1) and reduced EC viability, which were reversed by monosialoganglioside‐containing nanoliposomes. Interleukin‐8 production was augmented when astrocytes were exposed to medin‐treated ECs or their conditioned media. Conclusions: Cerebral arterial medin is higher in VaD compared with cognitively normal patients. Medin induces EC immune activation that modulates astrocyte activation, and its effects are reversed by monosialoganglioside‐containing nanoliposomes. Medin is a candidate novel risk factor for aging‐related cerebrovascular disease and VaD.